The Problems Arising in the Independent Education System and the Role of Women in the Field (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article provides information about the problems that arose in the educational system of Uzbekistan on the eve of independence. The ideology of the colonial state carried out in the educational system, the process of the Soviet "cultural revolution" event, overideologicalizing all aspects of society, especially science and culture, and covering every area of it, and its impact on the current era, education, science an attempt was made to reveal the activities of women in the field of science and the processes of education on the basis of several research data.